A Case of Marjolin’s Ulcer – High-Resolution Ultrasound Findings with a Review of Literature - Deka, Jeena Bordoloi; Shah, Ritu; Shah, Mohit Veer Kumar; Fermín, Miguel Jimenez; Dahiya, Nirvikar; Díaz, Fernando Jiménez (Archives of Clinical and Medical Case Reports, 2024)
Marjolin’s ulcer is a cutaneous malignancy that arises from previously damaged skin, long-standing scars, chronic wounds such as burns, chronic venous ulcers, pressure ulcers, chronic osteomyelitis, or sinuses. Burn scars are the most common lesion leading to this malignancy. Marjolin’s ulcer affects 1% to 2% of all burn scars. We present a case of Marjolin’s ulcer occurring in an old burn scar in a 46-year-old female, focusing on the high-resolution ultrasound features and its role in its management. Ultrasound was found to be helpful not only in evaluating the extent and depth of the lesion, but also in indicating the likelihood of malignant transformation. Histopathology confirmed it to be a squamous cell carcinoma. A wide excision with skin grafting was done. To the best of our knowledge, there is no literature reporting the ultrasound evaluation and findings of Marjolin’s ulcer.